PERANAN ADVOKAT DALAM MEWUJUDKAN AKSES KEADILAN MELALUI BANTUAN HUKUM - Sasta Humayra Aesta Himawan Putri (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This research discusses in depth the views and experiences of an advocate named Mr. Panca Andrian Pikter, regarding the implementation of legal aid in Indonesia, including structural limitations and implementation constraints that occur in the field. Some of the main obstacles found include budget limitations, lack of competent human resources, and low legal literacy in the community. In addition, the role of advocates in assisting justice seekers is important in filling the gap between the legal needs of the community and the capacity of legal service providers. This research also evaluates the effectiveness of Law No. 16/2011 on Legal Aid, as well as the utilization of digital technology in expanding the reach and efficiency of legal aid services.